The Metabolic Chemical Reporter Ac46AzGal Could Incorporate Intracellular Protein Modification in the Form of UDP-6AzGlc Mediated by OGT and Enzymes in the Leloir Pathway - Wang, Jiajia; Dou, Biao; Zheng, Lu; Cao, Wei; Dong, Peiyu; Chen, Yingyi; Zeng, Xueke; Wen, Yinhang; Pan, Wenxuan; Ma, Jing; Chen, Jingying; Li, Xia (Frontiers in Chemistry, 2021)
Galactose is a naturally occurring monosaccharide used to build complex glycans that has not been targeted for labeling as a metabolic reporter. We here characterize the cellular modification of proteins by using Ac46AzGal in a manner of concentration- and time-dependent. It is note that vast majority of this labeling of Ac46AzGal occurs intracellularly in a range of mammalian cells. We also provide evidence that labeling is not only dependent on the enzymes of OGT and OGA responsible for O-GlcNAcylation, but also the enzymes of GALT and GALE in Leloir pathway. Notably, these discoveries support the conclusion of substrate promiscuity of OGT, highlighting the possibility that intracellular O-galactose modification may be a widespread event under certain conditions, such as galactosemias, characterized with impaired function of the Leloir pathway of galactose metabolism.